(untitled) - Nguyễn, Hiếu Trung (Wageningen, 1998)
This study aim to apply the system development methodology to develop a prototype GIS for land use planning in the coastal are of MeKong Delta, VIETNAM. The system was designed though three main phase: system analysis, system design and system implementation.
Keywords: Soil acidity,Soil science